2020
DOI: 10.1080/15265161.2020.1764141
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Categorical Exclusion Criteria in Crisis Standards of Care Frameworks

Abstract: During public health crises including the COVID-19 pandemic, resource scarcity and contagion risks may require health systems to shift-to some degree-from a usual clinical ethic, focused on the well-being of individual patients, to a public health ethic, focused on population health. Many triage policies exist that fall under the legal protections afforded by "crisis standards of care," but they have key differences. We critically appraise one of the most fundamental differences among policies, namely the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…Because of this there is great debate over the use of quality-adjusted life years in policy making [46]. Even when purportedly "objective" criteria are used to allocate health care resources, subjective notions and ideas about the quality or desirability of life with disabilities may play an influential role [47].…”
Section: Concern For Disability Discrimination During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this there is great debate over the use of quality-adjusted life years in policy making [46]. Even when purportedly "objective" criteria are used to allocate health care resources, subjective notions and ideas about the quality or desirability of life with disabilities may play an influential role [47].…”
Section: Concern For Disability Discrimination During the Pandemicmentioning
confidence: 99%
“…Having a human rights-based strategy in place before catastrophic events happen is key for a disability inclusive response [50]. The core principles of dignity, nondiscrimination, equality of opportunity, and accessibility should be central during resource allocation protocol development [47]. To create successful disability inclusive community-based responses, planners need to ensure that people with disabilities have roles and responsibilities in the design and implementation of the responses [50].…”
Section: Concern For Disability Discrimination During the Pandemicmentioning
confidence: 99%
“…During disasters, it is important that triage procedures be carefully decided upon to guide healthcare workers and standardise care (Sztajnkrycer, Madsen & Báez 2006 ; White & Lo 2020 ). Triage is a necessary process where need outstrips demand, and it is essential that triage decisions be based on the best available evidence (Auriemma et al 2020 ; Joebges & Biller-Andorno 2020 ).…”
Section: Triagementioning
confidence: 99%
“…Some of these recommendations deviate from the 2015 Guidelines with regard to the clinical/triage considerations as well. For example, recent recommendations have suggested that exclusion criteria should not be part of a triage protocol, due to their potentially discriminator effects, 25,26,31,32 and the Office for Civil Rights (OCR) at the United States Department of Health and Human Services (HHS) issued a bulletin 33 to ensure that institutions do not deny resources based on disability 34 or advanced age. 7 While the 2015 Guidelines include exclusion criteria, the list of criteria was revised from the draft 2007 guidelines to only include medical conditions that would fall under the revised definition of (short-term) survival (see the above section Definition of "Survival").…”
Section: Discussionmentioning
confidence: 99%